A novel design for stable self-assembly cubosome precursor-microparticles enhancing dissolution of insoluble drugs. (3rd August 2017) - Mei, Liling; Xie, Yecheng; Jing, Hui; Huang, Ying; Chen, Jintian; Ran, Hao; Pan, Xin; Wu, Chuanbin
Abstract: Cubosomes have been presented to enhance dissolution of insoluble drugs, but their applications are limited by the practical hurdles associated with both preparation and storage instability, resulting in drug delivery failure. In the present study, an innovative cubosome precursor-microparticles (CPMs) spray dried from an aqua-free precursor solution was developed to improve cubosome stability during both preparation and storage as well as to enhance the dissolution of insoluble drugs. These CPMs spontaneously self-assembled in situ forming homogeneous cubosome dispersion by hydration and disintegration after exposure to the aqueous medium. The stable cubosome dispersion was obtained from self-assembly (SA) of CPMs after administration instead of fragmentation of bulk cubic phase gel into cubosomes, which settled the preparation instability due to avoidance of high energy fragmentation (e.g. ultrasonic effect, high speed shear and high pressure homogenization). Also, the subsequent storage instability issue can be excluded as the CPMs were stored in a solid stable form. The CPMs disintegration and cubosome SA were demonstrated by the notable morphology variation and the distinct microparticle size decrease from CPMs (10–20 μm) to SA-cubosomes (150–200 nm). The cumulative release of docetaxel (DTX, model insoluble drug) incorporated in CPMs increased to 96.4% within 120 minutes compared with only 75.2% for blank CPMs and DTX physical mixture, demonstrating that CPMs significantly enhanced the dissolution extent of insoluble drug. The SA-cubosomes possessed quite high drug entrapment efficiency (>95%) and an integrated drug dissolution content, which significantly increased the drug utilization rate.